Discourses surrounding 'race', equity, disadvantage and transformation in times of rapid social change : higher education in post-apartheid South Africa - Robus, Donovan (Rhodes University, Faculty of Humanities, Department of Psychology, 2005)
Since the dismantling of Apartheid in South Africa in 1994, the South African socio-political and economic landscape has been characterised by rapid change. In the ten years since the 'new' democratic South Africa emerged, transformation has become a dominant discourse that has driven much action and practice in a variety of public areas. One of the areas of focus for transformation has been Higher Education whereby the Department of Education aimed to do away with disparity caused by Apartheid segregation by reducing the number of Higher Education institutions from 36 to 21. This research draws on Foucauldian theory and post-colonial theories (in particular Edward Said and Frantz Fanon), and the concept of racialisation in an analysis of the incorporation of Rhodes University's East London campus into the University of Fort Hare. Ian Parker's discourse analytic approach which suggests that discourses support institutions, reproduce power relations and have ideological effects, was utilised to analyse the talk of students and staff at the three sites affected by the incorporation (viz. Rhodes, Grahamstown, Rhodes, East London and Fort Hare) as well as newspaper articles and public statements made by the two institutions. What emerged was that in post-Apartheid South Africa, institutional and geographic space is still racialised with virtually no reference to the historical and contextual foundations from which this emerged being made. In positioning space and institutions in this racialised manner a discourse of 'white' excellence and 'black' failure emerges with the notion of competence gaining legitimacy through an appeal to academic standards. In addition to this, transformation emerges as a signifier of shifting boundaries in a post-Apartheid society where racialised institutional, spatial and social boundaries evidently still exist discursively.
Keywords: Rhodes University; University of Fort Hare; Universities and colleges -- Mergers -- South Africa; Education, Higher -- South Africa; Education and state -- South Africa; Apartheid -- South Africa; Discourse analysis -- Methodology; Discrimination in education -- South Africa; Educational change -- South Africa